Social Sciences and Social Change - Dilnawaz A. Siddiqui (International Institute of Islamic Thought, 1991)
The second decade of the association's existence culminated in a very encouraging conference in Dearborn, Michigan this year. The conference highlights included a keynote address by Ali Mazrui, Albert Schweitzer Professor in the Humanities, State University of New York at Binghamton, and addresses by 'AbdulHamid AbuSulayman, past president of AMSS and current rector of the Islamic University of Malaysia, and Munir Ahmad Khan, director of the Pakstan Atomic Energy Commission. Mazrui, who focused on the Gulf crisis, spoke about the double standards practiced by the West in dealing with the Muslim ummah. AbuSulayman stressed the need for reform of character at the individual level for achieving lasting social change. The Isma'il and Lamya' al Faruqi Memorial Lecture was delivered by John Esposito, director of the Center for International Studies, Holy Cross College, Worcester, Massachusetts and past president of the Middle East Studies Association (MESA). He reminded the Muslim social scientists of Isma'il al Faruqfs tradition, urging them to become activists and scholars of Islam at the same time. The conference proceedings were spread over nineteen panels which offered a variety of papers on Islam and Muslim life by scholars from North America and overseas. The tradition that had been revived three years ago was maintained, and thus the Association of Muslim Scientists and Engineers (AMSE) also held their annual conference concurrently with this year's AMSS conference. The other tradition that continued was the trialogue between representatives of the three Abrahamic faiths. Another feature of the program was the incorporation of the AMSS Business Administration seminar. This program featured two panels. In the first panel, Ahmed M. Abo-Hebeish of Northrop Corporation discussed the framework of debtor-creditor relations as the foundation of financial accounting in Islam, and Mohamed A. El-Badawi of California State University addressed the issue of computing zakatable funds. The other panel (Session 5: Panel 10) in this discipline had four presentations. The seminar chairman, Ghouse A. Shareef of Bellannine College in Kentucky, spoke on "Acountability, Congruency, and Equilibrium as the ...